Between Past and Future - 1/19
Continuation of Prof. Professor Miklós Haraszti’s speech and the closing of the panel entitled “Vulnerabilities of the New Democracies.” Chairman John Lampe (Professor at the University of Maryland) is closing this fourth panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999, by providing the concluding remarks and inviting the audience to debate the issues discussed. Responding the audience’s questions are the members of the panel Katherine Verdery (Professor at the University of Michigan), Gail Kligman (University of California Los Angeles), Kazimierz Poznanski (Professor at the University of Washington), István Rév (Professor at CEU and Director of the OSA Archives) and Miklós Haraszti (Hungarian Writer, Journalist and Professor).